Praktik Penadahan Hasil Pencurian Sepeda Motor Di Kabupaten Bima - Hajairin Hajairin (Universitas Mahendradatta, 2020)
The practice of deterrence of the results of motorcycle theft in Bima Regency, actually there are different criminal acts, namely criminal detention and theft, in the criminal offense is regulated in Article 480 of the Criminal Code (KUHP) while criminal acts of theft are set in Article 362 of the Criminal Code (KUHP), besides that many people use stolen motorbikes also make it easy for anyone to steal motorbikes, because thieves have no difficulty in selling their stolen products, whereas deterrence of the results of motorcycle theft is a crime committed by a third party as a host, with the intention of benefiting from the results of motorcycle theft committed by another person. The crime of motorcycle theft in the Regency of Bima, appears as a new social problem, collectors not only collect , deviating the results of motorcycle theft in the local area in the district of Bima only, but also can receive motorbike theft and embezzlement of motorbikes in other areas such as the island of Lombok, Java and Jakarta etc. This dynamic explains the existence of structural crimes in motorcycle theft in Bima Regency, the structural can be deterrence in Bima Regency in collaboration with collectors outside Bima Regency to facilitate the deviation of the results of the motorcycle theft